2017
DOI: 10.1038/s41598-017-01230-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of Cancer Cells by Oxidative Vulnerabilities with Novel Curcumin Analogs

Abstract: Recently, research has focused on targeting the oxidative and metabolic vulnerabilities in cancer cells. Natural compounds like curcumin that target such susceptibilities have failed further clinical advancements due to the poor stability and bioavailability as well as the need of high effective doses. We have synthesized and evaluated the anti-cancer activity of several monocarbonyl analogs of curcumin. Interestingly, two novel analogs (Compound A and I) in comparison to curcumin, have increased chemical stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 59 publications
(44 reference statements)
0
36
0
Order By: Relevance
“…Moreover, although cancer cells have developed redox adaptation mechanisms to survive in a high oxidative environment, extensive studies have suggested that they are more vulnerable to oxidative stress caused by ROS-generating agents than normal cells, providing the selectivity of ROS-based therapies 197 . Exogenous ROS-generating agents used as a single agent or in combination with other standard therapies have shown promise in pre-clinical studies 198 200 .…”
Section: Cell Death and Disease Treatmentmentioning
confidence: 99%
“…Moreover, although cancer cells have developed redox adaptation mechanisms to survive in a high oxidative environment, extensive studies have suggested that they are more vulnerable to oxidative stress caused by ROS-generating agents than normal cells, providing the selectivity of ROS-based therapies 197 . Exogenous ROS-generating agents used as a single agent or in combination with other standard therapies have shown promise in pre-clinical studies 198 200 .…”
Section: Cell Death and Disease Treatmentmentioning
confidence: 99%
“…Additionally, by inhibiting NF-κB signaling, curcumin was able to increase cellular uptake of gemcitabine and decrease desmoplasia, and thus decrease chemoresistance [ 238 ]. Preclinical trials have shown that curcumin can work both alone and in combination with chemotherapy to generate anti-PDAC effects [ 80 , 239 ]. In an early xenograft study, curcumin potentiated the effectiveness of gemcitabine in suppressing PDAC tumor formation significantly by ca.…”
Section: Dietary Considerationsmentioning
confidence: 99%
“…Several downstream mechanistic studies revealed that the remarkable anti-cancer properties of these diarylpentanoids are due to their anti-angiogenic and apoptosis-inducing activities, which resulted from VEGF inhibition and caspases activation, respectively [ 26 , 27 , 28 ]. In addition, cyclic monocarbonyl diarylpentanoids were also found to be effective in-vivo based on their positive suppression against tumor growth in several mice xenograft models [ 29 , 30 ]. Interestingly, recent studies demonstrated that this diarylpentanoid family possesses a curcumin-like safety profile as they were shown to be non-toxic in acute toxicity evaluations of several anti-inflammatory animal models [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%